Transfer Iptek Mathematic Realistic Worksheet Berbasis ICT Kepada Guru-Guru SDIT dalam Rangka Meningkatkan Keterampilan Matematis pada Konsep Geometris - Usman Arifin; Ratni Purwasih; Fifiet Dwi Tresna Santana (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
Mathematics is a human activity carried out in daily life both consciously and unconsciously such as measurement (geometry) or arithmetic calculations, but in its implementation there are still many who find it difficult to understand mathematics. The availability of instructional media is one of the factors that is less optimal in class learning. The activity of this community partnership program aims to introduce Information and Communication Technology(ICT) in learning and provide training to design teaching materials using ICT. The methods of implementing community partnership activities are training, the formation of a training team for trainers (TFT) and ICT-based teaching materials. The results of the implementation of these community partnership activities are the activities of the community partnership program by conducting training by transferring knowledge and technology to create learning designs for mathematical realistic worksheets based on ICT to get positive responses from SDIT teachers in one of West Bandung regencies. ICT training for mathematics teachers must be developed so that they are more skilled in using ICT in the learning of mathematics in class and are skilled at making ICT-based learning designs and to make use of them in the revolutionary 4.0 era.